A Single‐Crystal Co‐Base Superalloy Strengthened by γ′ Precipitates: Structure and Mechanical Properties[a]. Issue 6 (20th April 2015) - Petrushin, Nikolay; Hvatzkiy, Konstantin; Gerasimov, Victor; Link, Thomas; Epishin, Alexander; Nolze, Gert; Gerstein, Gregory
<x xml:space="preserve">Abstract</x> An experimental Co‐base superalloy was designed from the Ni‐base system by exchange of Ni and Co concentrations. The alloy consist of a Co‐matrix (γ phase) strengthened by cuboidal precipitates Co3(Al, X) (γ′ phase). The γ′‐solvus temperature is 1 005 °C. [001] single crystals of this alloy were solidified and tested for tension at different temperatures up to 1 000 °C. It was found that the Co‐base alloy has a much lower yield stress than a corresponding Ni‐base alloy, but a much higher ductility. The partitioning behaviour of the alloying elements in the Co‐base alloy and the deformation mechanisms were investigated by scanning and transmission electron microscopy.